Perceptions of caring behaviour among undergraduate nursing students in Gandaki Province, Nepal - Devi Ghimire, Gita; Sigdel, Sujita (Journal of Chitwan Medical College, 2025)
Introduction: Nurses' caring behaviour is an important aspect of nursing services requiring both relevant scientific knowledge and professional skills. Caring competence is an aspiration for nursing students. This study aims to assess perception of caring behaviour among undergraduate nursing students. Method: A descriptive cross-sectional design was adopted to assess perceptions of caring behaviour. Three nursing colleges were selected purposively from Gandaki province, Nepal. Students from BSc and BNS streams were included by total enumerative sampling method. Students from different classes and academic years were selected by lottery. Self-administered structured questionnaire was used to collect data. Caring Behaviour Inventory-16 student version scale was used to measure the perception. The IBM SPSS was used for descriptive and inferential statistics (chi-square) with a significance level of p<0.05. Result: Out of 381 students, 297(78%) were of age ≤25 years (22.86±3.02). Most, 351(92.1%), chose nursing profession on their own interest. Almost all, 364(95.5%), had a positive perception about nursing. The overall perception of caring behaviour mean was 5.21±0.44. Sub-scale showed highest mean score (5.36±0.54) for respectful domain and lowest for connectedness (5.00±0.61). Perception of caring behaviour was significantly associated with age, educational level, class level, attitude toward clinical supervisor, duration of clinical exposure and previous hospital employment. Conclusion: This study found that undergraduate nursing students had a good perception of caring behaviour. Caring behaviour was associated with age, educational level, class, attitude toward clinical supervisor, and clinical exposure. Thus, it’s possible to enhance nurses' caring behaviour with proper intervention during school and work.